La Ratio studiorum de 1599 et la normalisation de la figure du contestataire au sein des collèges de la Compagnie de Jésus - Véronique Castagnet‑Lars (Les Cahiers de Framespa)
The recent historiography of student history invites us to re-read “the Genealogy of the ratio Studiorum” of 1599 (Dominique Julia) in order to highlight the work of the first two generations of Jesuit teachers concerning the typical profile of the troublemaker, a type of student one would not expect to find in a Jesuit school whose teachers, as historians have insisted upon so far, perfectly master discipline. During the second half of the 16th century, the first educationalists elaborated training agendas for each new foundation and exchanged rich correspondence. Local experiences were thus grouped and, implicity, led to the adoption of indicators allowing to identify a “protester”, or even to decide the exclusion of some students, while their instruction, catholic here, remained a goal in the context of religious denominational confrontations.